The impact of low intensity ultrasound on cells: Underlying mechanisms and current status - Du, Meng; Li, Yue; Zhang, Qing; Zhang, Jiaming; Ouyang, Shuming; Chen, Zhiyi (Progress in biophysics and molecular biology, 2022)
Low intensity ultrasound (LIUS) has been adopted for a variety of therapeutic purposes because of its bioeffects such as thermal, mechanical, and cavitation effects. The mechanism of impact and cellular responses of LIUS in cellular regulations have been revealed, which helps to understand the role of LIUS in tumor treatment, stem cell therapy, and nervous system regulation. The review summarizes the bioeffects of LIUS at the cellular level and its related mechanisms, detailing the corresponding theoretical basis and latest research in the study of LIUS in the regulation of cells. In the future, the design of specific LIUS-mediated treatment strategies may benefit from promising investigations which is hoped to provide encouraging therapeutic data.Low intensity ultrasound (LIUS) has been adopted for a variety of therapeutic purposes because of its bioeffects such as thermal, mechanical, and cavitation effects. The mechanism of impact and cellular responses of LIUS in cellular regulations have been revealed, which helps to understand the role of LIUS in tumor treatment, stem cell therapy, and nervous system regulation. The review summarizes the bioeffects of LIUS at the cellular level and its related mechanisms, detailing the corresponding theoretical basis and latest research in the study of LIUS in the regulation of cells. In the future, the design of specific LIUS-mediated treatment strategies may benefit from promising investigations which is hoped to provide encouraging therapeutic data.